"A Bigoted, Prejudiced, Hateful Little Area": The Making of an All-White Suburb in the Deep North. (March 2019) - Montrie, Chad
This article traces the history of Edina, Minnesota, a community just outside of Minneapolis, following its transformation from an interracial farming village in the late nineteenth century to a racially exclusive and prejudice-ridden "streetcar" suburb by the 1930s. It also looks at the ordeal experienced by the first black family to move to the area, in 1960, demonstrating the challenges faced by the "open housing" movement in what is known as a racially "progressive" state. As a history of demographic change, the article suggests the need for a slightly revised Great Migration narrative, particularly when African Americans moved north and when and why some of the first migrants moved to cities. Likewise, it contributes to a literature showing how northern suburban communities became and remained all white for nearly a century and, more generally, how pervasive and intransigent racism was even among well-mannered, middle-class white Americans in the Deep North.